The Association between Resting Heart Rate and Urinary Albumin/Creatinine Ratio in Middle-Aged and Elderly Chinese Population: A Cross-Sectional Study - Wenfeng Mao; Xinye Jin; Haibin Wang; Yingnan Ye; Linxi Zhang; Shi Gu; Jie Wang; Guang Ning; Yiming Mu (Journal of Diabetes Research)
Objective. In general population, resting heart rate (RHR) is associated with cardiovascular disease. However, its relation to chronic kidney disease (CKD) is debated. We therefore investigated the relationship between RHR and urinary albumin/creatinine ratio (UACR, an indicator of early kidney injury) in general population at different levels of blood pressure and blood glucose. Methods. We screened out 32,885 subjects from the REACTION study after excluding the subjects with primary kidney disease, heart disease, tumor history, related drug application, and important data loss. The whole group was divided into four groups (Q1: RHR≤71, Q2: 72≤RHR≤78, Q3: 79≤RHR≤86, and Q4: 87≤RHR) according to the quartile of average resting heart rate. The renal function was evaluated by UACR (divided by quartiles of all data in the center to which the subject belonged). Ordinary logistic regression was carried out to explore the association between RHR and UACR at diverse blood pressure and blood glucose levels. Results. The subjects with higher RHR quartile tend to have a higher UACR, even multifactors were adjusted. After stratifying the subjects according to blood pressure and blood glucose, the positive relationship between RHR and UACR remained in the subjects with normal blood pressure and normal glucose tolerance, while in the hypertension (SBP≥140 mmHg and/or DBP≥90 mmHg) group and the diabetic mellitus (FPG≥7.0 mmol/L and/or PPG≥11.1 mmol/L) group, the relationship disappeared. In the subjects without hypertension, compared with the Q1 group, the UACR is significant higher in the Q3 group (OR: 1.11) and the Q4 group (OR: 1.22). In the subjects with normal glucose tolerance (NGT), compared with the Q1 group, the UACR is significantly higher in the Q3 group (OR: 1.13) and the Q4 group (OR: 1.19). Conclusions. The population with higher RHR tend to have a higher UACR in the normal blood pressure group and the normal glucose tolerance group.